Levels, enrichment characteristics and dietary intake risk of polychlorinated dibenzo-p-dioxin/furans in traditional smoked pork. (1st July 2023) - Yang, Xinrui; Chen, Wenming; Jin, Jun; Hu, Jicheng
Abstract: The concentrations and TEQs of polychlorinated dibenzo-p-dioxin/furans (PCDD/Fs) in traditional smoked pork were significantly higher than those in raw pork, and mainly distributed in the surface layer. The main enriched congeners during traditional smoking were 2378-TCDF, 12378-PeCDF, 23478-PeCDF, 1234678-HpCDF, OCDF, 1234678-HpCDD and OCDD. The ability of each congener to transfer from the surface to the inner part was various. According to the dietary habits of local residents, PCDD/Fs in more than half of the traditional smoked pork samples posed a potential carcinogenic risk, and the risk in the surface samples were 1.02–10.2 times that of the corresponding inner samples. Some variables might be the important factors affecting the concentration of PCDD/Fs in smoked pork, such as the duration of smoking and the kind of fuel. It is recommended to achieve lower risk by reducing the consumption of smoked pork, especially the surface layer of smoked pork, and innovating traditional smoking technologies. Graphical abstract: Image 1 Highlights: Traditional smoking way cause significant contamination of PCDD/Fs in pork. More PCDD/Fs distributed in the surface of traditional smoked pork. The transfer capability of 17 PCDD/F congeners in smoked pork is different. PCDD/Fs in traditional smoked pork may pose potential health risks to consumers. Duration of smoking and fuel type are important factors affecting PCDD/F level.